2022
DOI: 10.1155/2022/8946094
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis Method for Rolling Bearing Based on Sparse Principal Subspace Discriminant Analysis

Abstract: Rolling bearings are omnipresent parts in industrial fields. To comprehensively reflect the status of rolling bearing and improve the classification accuracy, fusion information is widely used in various studies, which may result in high dimensionality, redundancy information of dataset, and time consumption. Thus, it is of crucial significance in extracting optimal features from high-dimensional and redundant feature space for classification. In this study, a fault diagnosis of rolling bearings model based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…X iA ) T . The particle is then updated by each iteration of the individual and extreme global values, with the velocity and position defined in Equations ( 2) and (3) [90].…”
Section: Pso-bp Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…X iA ) T . The particle is then updated by each iteration of the individual and extreme global values, with the velocity and position defined in Equations ( 2) and (3) [90].…”
Section: Pso-bp Neural Networkmentioning
confidence: 99%
“…In this paper, particle number n was set as 20, learning factors c 1 and c 2 were kept the same as 2 and momentum coefficients r 1 and r 2 were kept the same as 0.8 [90]. Inertia weight ω was assigned to 0.8 after several trials.…”
Section: Pso-bp Neural Networkmentioning
confidence: 99%
“…At present, the bearing fault diagnosis technology has been widely developed, but there are still problems in the research of bearing fault diagnosis, such as insufficient researches on fault symptoms and fault mechanisms, however, the fault mechanism research is an important foundation and basis for the fault prediction and safety guarantee of key equipment [7].On the basis of mechanical vibration theory, SKF of Sweden and Franklin Institute of the United States [8] cooperated to study the vibration of ball bearings, and put forward a free circular bending vibration model of bearing vibration; Li Yuqi et al [9] analyzed different initial deformation and bearing clearance by establishing a nonlinear rotor system dynamics model and solving the equations of motion of the rotor system by the Newmark-method, and then analyzed the impact of different initial deformation and bearing clearance on the nonlinear vibration of the rotor system. on the nonlinear vibration characteristics of the rotor system; Zhu Yongsheng et al [10] used the Lempel-Ziv method to quantify the bearing vibration signals and established a dynamics model containing six degrees of freedom to study the effect of compound faults on the vibration response of the bearings; Yuan et al [11] constructed a new multi-body dynamics model of the bearing system to study the evolution of compound defects and analyzed the effect of defect evolution on vibration response characteristics; Pandya et al [12] used an adaptive algorithm of wavelet decomposition and Hilbert transform to extract bearing fault feature components from vibration signals, and investigated the nonlinear dynamic response caused by compound faults; Luo Jianing et al [13,14] showed that vibration features obtained from the simulation model can provide effective sample data for the study of bearing fault diagnosis methods, and can be used as a supplement to the fault dataset (S1 Data).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, deep learning and machine learning have been developed continuously, and their outstanding feature extraction and data processing capabilities are widely used in rolling bearing fault diagnosis. Zhou et al [6] combined the vibration signal into image signal with structural reparameterization technique to achieve rolling bearing fault diagnosis. Liu et al [7] decomposed the original bearing signal into multiple multiscale signals by signal decomposition and transformation, and the multiscale signals were used as the corresponding input channels, and the outputs of parallel subneural networks were connected into one channel as the input of the fully connected layer for classification.…”
Section: Introductionmentioning
confidence: 99%